Agile Leadership: Empowering Millennial Performance through Talent Management and Corporate Culture - Zulham, Muhammad; Nurhayati, Mafizatun (Adpebi International Journal of Multidisciplinary Sciences, 2025)
Purpose – This study aims to examine the impact of agile leadership on the performance of BTN millennial employees, mediated by talent management and corporate culture Methodology/approach – This study involves Bank BTN employees, referred to as BTNers, categorized as Millennials, selected through purposive sampling. Data were collected using questionnaires and analyzed using the Partial Least Squares (PLS) method with SmartPLS version 3 software Findings – This research demonstrates that agile leadership significantly influences performance, talent management, and corporate culture. Furthermore, talent management and corporate culture significantly impact performance. Additionally, it was found that talent management and corporate culture can mediate the effect of agile leadership on employee performance Novelty/value – This study delves deeper into the role of agile leaders in shaping talent management and corporate culture, which are crucial for the performance of millennial employees—often characterized as vulnerable and lacking resilience—making this research highly relevant for discussion